Effectiveness of Educational Health Program on Nurses Knowledge toward Post-Operative Care for the Child undergoing Cardiac Surgery inPediatricCardiac Intensive CareUnit (PCICU) at Cardiac Centers and Hospitals in Baghdad City - Ghanim , Mohammed A.; Obaid, Khamees Bandar; Obaid, Khamees Bandar; Obaid, Khamees Bandar (International Journal of Psychosocial Rehabilitation, 2020)
Background:Congenital heart defects (CHD) are anatomic malformations that found at delivery and result due to abnormal cardiac function, and considered as the main cause of death in the first 12 months of life. Surgical Operation has been the gold standard treatment for congenital cardiac anomalies or malformations for decades, it has significantly reduced the morbidity and mortality of infants born with severe and complicated cardiac conditions, with development in the field of congenital cardiac surgery, various complex actions are done in children. These moves can be having numerous complications, nurse must be have an information and skills to provide best nursing care postoperatively to the children with congenital heart disorders and children undergoing cardiac surgery.Methodology:The study was designed as quasi-experiment for study group and control group participants employed in cardiac intensive care unit of cardiac centers and hospitals in Baghdad city (Ibn Al-Nafees Hospital, Iraqi Center for Heart Disease, and Ibn Al-Bitarcenter for cardiac surgery), being tested in two periods pre-test, and post-test , The study group participants are tested prior implementing the educational program (the educational program lectures started from 4th -22th of March 2020, In the CICU departments) then after period they are tested post-test (2th - 14th April, 2020 in same CICU departments). The control group participants are provided with the same questionnaire to answer at same time intervals as in study group but without enrollment in educational program.The results:The results of the study show that the effectiveness of educational program about nurses’ knowledge regarding post-operative care for the child undergoing cardiac surgery.Discussion:there is a highly significant difference in study group between pre and post-test in all main domains related to post-operative care for the child undergoing cardiac surgery.Conclusion:Most of nurses in Cardiac intensive care units had knowledge deficit concerning post-operative care for the child undergoing cardiac surgery. There were no differences between the knowledge in both study and control groups in the pretest. There is an improvement in the knowledge of the nurses in study group after exposure to an educational program concerning post-operative care for the child undergoing cardiac surgery, there were no significant differences between pre and posttest of control group in all main domains except in the sixth domain concern postoperative care. The effectiveness of program show strong difference between the nurses’ knowledge for both study and control groups during the post-test.